Toward carbon neutrality: The transition of the coal industrial chain in China - Zhong, Chen; Dong, Fanli; Geng, Yong; Dong, Qiuxia (Frontiers in Environmental Science, 2022)
In order to achieve China’s ambitious carbon neutrality target, coal industry should play a key role on mitigating its carbon emission and ensuring energy supply. Therefore, it is urgent for this coal industry to realize its transition toward low carbon development. This study investigates the status and policy options of China’s coal industry by considering the entire coal industrial chain, covering coal production, delivery, and consumption so that key challenges involving clean and efficient utilization and stable coal supply can be identified. Further, policy recommendations for the transition of this coal industrial chain toward low carbon development are proposed, including the implementation of appropriate national policies, research and development (R&D) efforts, the application of economic instruments and capacity building activities.